Relative condition factor, length-weight relationship, and growth of three-spotted flounder, Pseudorhombus triocellatus from Parangipettai Coast, India - PALANIVEL BHARADHIRAJAN; GOPALAN MAHADEVAN; PERUMAL MURUGESAN; SAMANTHAM MURUGAN; MOJTABA POULADI; REZA ABBASPOUR NADERI (Biodiversitas Journal of Biological Diversity, 2019)
Bharadhirajan P, Mahadevan G, Murugesan P, Murugan S, Pouladi M, Abbaspour Naderi R. 2019. Relative condition factor, length-weight relationship, and growth of three-spotted flounder, Pseudorhombus triocellatus (Bloch & Schneider, 1801) from Parangipettai Coast, India. Biodiversitas 20: 373-379. The three-spotted flounder, Pseudorhombus triocellatus is usually caught as trawl by-catch from Parangipettai coastal waters but regrettably, limited information on its age structure and growth is available. Hence, the present study aims to understand some basic parameters of its biology and growth. A total of 759 specimens (360 males and 399 females) ranging from 4 cm to 13 cm in total length (TL) and 5.26-35.41 g in weight were collected from the trawl catches of Parangipettai and Mudasalodai landing center during January–December 2015. The estimated growth coefficient (b) value for males (2.797) was greater than 3 and for females (3.023) was less than 3. The relative condition factor (Kn) values of females were higher than males except during February, June, and September. The values of asymptotic length (L?) obtained in this study using various methods didn’t vary significantly (P>0.05). The most appropriate values of asymptotic length (L?) for males were 137.11 mm and for females were 141.75 mm. The most appropriate values of growth rate (K) for males were 0.397 yr-1 and for females were 0.410 yr-1. The estimated length at age 0 (t0) for males and females were 0.197 mm and 0.292 mm, respectively. The longevity (tmax) of males and females P. triocellatus were 2.04 years and 2.24 years, respectively. The result of this study provides basic information for future studies.